Genteel Rebel : The Life of Mary Greenhow Lee - Phipps, Sheila R., 1948- (Book collections on Project MUSE., 2004)
As a Confederate sympathizer in the hotly contested small border town of Winchester, Virginia, she ran an underground postal service, hid contraband under her nieces' dresses, abetted the Rebel cause, and was finally banished."--Jacket.